National Security of Mongolia: Past, Present & Future - Batchimeg, Mijeddorj (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i17.79 Mongolian Journal of International Affairs, No.17 2012: 12-17